2013
DOI: 10.1590/s1516-89132013000100020
|View full text |Cite
|
Sign up to set email alerts
|

Properties of a biosurfactant produced by Bacillus pumilus using vinasse and waste frying oil as alternative carbon sources

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
1
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(25 citation statements)
references
References 25 publications
1
19
1
4
Order By: Relevance
“…The CMC of SDS is 2100 mg L À1 . 32,33 Compared with synthetic surfactants, the three rhamnolipid products are highly excellent.…”
Section: Emulsifying Activity Of the Three Rhamnolipid Productsmentioning
confidence: 99%
“…The CMC of SDS is 2100 mg L À1 . 32,33 Compared with synthetic surfactants, the three rhamnolipid products are highly excellent.…”
Section: Emulsifying Activity Of the Three Rhamnolipid Productsmentioning
confidence: 99%
“…This demonstrates the excellent stability of the microorganism, which is one of the desirable requirements for microorganisms used in industry (Schmidell et al, ). In addition, B. pumilus produced greater efficiency in the reduction of surface tension when compared to other studies that used the same bacterium (Calvo et al, ; Fooladi et al, ; Oliveira and Garcia‐Cruz, ; Sharma et al, ).…”
Section: Resultsmentioning
confidence: 61%
“…Haddad et al [37] found that biosurfactat production by B. subtilis HOB2 was growthassociated, since the strain produced surfactant within 24 h of incubation. However, in the study of Oliveira and Garcia-Cruz [38] with B. pumilus, the biosurfactant biosynthesis in medium containing vinasse or frying oil as carbon source, was not growth-associated.…”
Section: Discussionmentioning
confidence: 87%